Ubuntu! : an inspiring story about an African tradition of teamwork and collaboration - Lundin, Stephen C., 1941-; Nelson, Bob, 1956- (New York : Broadway Books, 2010)
A powerful story about the African philosophy of teamwork and collaboration that has the power to reshape our workplaces, our relationships with our coworkers, and our personal lives. John Peterson, a new manager in the credit department at a major big-box retailer, is struggling in his job. The people under him are not working as well or effectively as they need to, and his department is falling behind in meeting its goals. His only solution is to take on more work himself, burning the midnight oil and coming in most weekends to pick up the slack and keep his department above water. When one of the employees stays behind to help him-a young man who came to America from a small village in Africa-he learns of the ancient wisdom and hidden power of the African philosophy of Ubuntu. Before long, it begins to change the way he thinks about the people he works with, about himself, and about how he runs his department and his life. In an engaging and completely fresh narrative that holds a unique message for today's business world, Ubuntu! shows us a way to overcome our fears, insecurities, and the "me-ism" that so often permeates our workplaces, and replace it with a culture of genuine respect and collaboration.
Keywords: Employee motivation; Teams in the workplace; Interpersonal relations; Corporate culture; Management